Evolution of major non‐HIV‐related comorbidities in HIV‐infected patients in the Italian Cohort of Individuals, Naïve for Antiretrovirals (ICONA) Foundation Study cohort in the period 2004–2014. Issue 2 (21st November 2018) - d'Arminio Monforte, A; Diaz‐Cuervo, H; De Luca, A; Maggiolo, F; Cingolani, A; Bonora, S; Castagna, A; Girardi, E; Antinori, A; Lo Caputo, S; Guaraldi, G; Cozzi‐Lepri, A; et al.
Abstract : Objectives: The management of HIV disease is complicated by the incidence of a new spectrum of comorbid noncommunicable diseases (NCDs). It is important to document changes in the prevalence of NCDs over time. The aim of the study was to describe the impact of ageing on HIV markers and on the prevalence of NCDs in people living with HIV (PLWHIV) in the Italian Cohort of Individuals, Naïve for Antiretrovirals (ICONA) seen for care in 2004–2014. Methods: Analyses were conducted separately for a closed cohort (same people seen at both times) and an open cohort (all people under follow‐up). We used the χ 2 test for categorical factors and the Wilcoxon test for quantitative factors to compare profiles over time. Results: The closed cohort included 1517 participants and the open cohort 3668 under follow‐up in 2004 and 6679 in 2014. The median age of the open cohort was 41 [interquartile range (IQR) 37–46] years in 2004 and 44 (IQR 36–52) years in 2014. Analysis of the closed cohort showed an increase in the prevalence of some NCDs [the prevalence of dyslipidaemia increased from 75% in 2004 to 91% in 2014, that of hypertension from 67 to 84%, and that of cardiovascular disease (CVD) from 18 to 32%] and a decrease in renal function (5% with eGFR < 60 mL/min per 1.73 m 2 in 2004 versus 30% in 2014); the percentage of people in the high‐risk group for the Framingham CHD score more than tripled (from 13 to 45%). Results in the open cohort were similar. Conclusions: The burden of NCDs in our PLWHIV population markedly worsened over a 10‐year time‐span, which is likely to be a result of the effects of both ageing and HIV infection as well as their interaction. Special attention must be given to the management and prevention of NCDs.